The water issue between Malaysia and singapore: colonial legacy and post-colonial trajectory - Abdullah, A. Rahman Tang (s.n, 2012)
This research paper discusses the origins and historical development of water supply between Johor and Singapore from 1904 to 1941. It reveals events that preceded the formative stage of the water-supply scheme, analyses the 1927 water agreements and their implications, and examines the dynamics of water supply to Singapore before the Second World War. It demonstrates that the political framework of water supply between the two countries has been in favourable to Singapore simply as a matter of colonial legacy. In essence, Singapore has traditionally enjoyed a strategic advantage over Johor because the former is a developed country. Arguably, it has been one of the hallmarks of modern history that a developed country gains advantages by possessing capitalist supremacy over a developing country.